The dynamics of collaborative behaviour based on seating position in islamic education organisations - Gunarti Ika Pradewi; M. Abidin Arkham; Wahyuadi Nugroho; Nayla Anriana Riswari; Nurul Hidayah; Bayu Edi Nugroho (At Turots: Jurnal Pendidikan Islam, 2024)
Seating arrangements are often made in organisations. Seating changes can occur due to changes in organisational structure or room construction. The research aims to explore in depth how seating positions in the workspace shape and influence the dynamics of collaboration among members of an educational organization. Focusing on a private campus in Central Java, the researcher examines the unique context of the institution, aiming to identify interaction patterns naturally arising from seating arrangements that contribute to the formation of a collaborative environment. This study employs qualitative research methods, with informants selected using a purposive sampling technique. Data was collected through participatory observation and in-depth interviews. Furthermore, the data that has been collected is analysed using thematic analysis. The results show that, first, seating that is further apart or separated by physical barriers limits the intensity of interaction and tends to create more formal and structured communication patterns. Second, the dynamics of collaboration due to seating arrangements can be very different, depending on the personalities of individual members of the organisation. Third, seating arrangements and transfers are not a problem when the transferee is comfortable. This comfort can be achieved through the suitability of the physical and social environment